Analysis of factors associated with pornography viewing habits among adolescents - Rika Yuanita Pratama; Ida Dwi Rahayu; Ria Damayanti; Arum Seftiani Lestari; Atri Rudtitasari; Yunida Yunida (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Advances in digital technology have provided broader access to various types of information, including content that is inappropriate for certain age groups, such as pornography. A cross-national survey in Europe involving 10,930 adolescents found that in Indonesia, approximately 94% of adolescents are exposed to pornography; at the Mensiku Community Health Center, 17 cases of pornography consumption were recorded. Continuous exposure to pornography can have negative effects on adolescents. Purpose: To identify the factors associated with the habit of watching pornographic films among adolescents. Method: A quantitative research method with a cross-sectional design. The study population consists of all students at Junior High School 1 Binjai Hulu, with a sample of 69 respondents selected using proportional random sampling, analyzed via the Chi-Square Test. Results: A significant association between knowledge (p-value = 0.004), access to information (p-value = 0.001), the influence of peers (p-value = 0.012), and parental supervision (p-value = 0.001) and the habit of watching pornography among adolescents. Conclusion: Factors associated with the habit of watching pornographic films among adolescents include knowledge, access to information, the role of peers, and parental supervision. Keywords: Pornography; Teenagers; Viewing Habits.